Chapter 12 Computer science - Hartel, Pieter (Routledge International Handbooks, 2019)
In this chapter we will explore the relationship between crime and computers and networks by answering the following questions: •• Which techniques from computer science can be used to prevent crime? •• Which techniques from computer science can be used to study crime? To address the first question we use the 25 techniques of situational crime prevention to provide a systematic assessment of how computer and network technology can be used to prevent crime. The second question will be addressed by discussing computer simulation methods in cases where real experiments with crime prevention would be too costly or impractical.